PENDEKATAN PENDIDIKAN AGAMA ISLAM DALAM MENGATASI DELINQUENCY ANAK DAN REMAJA - Nur Ali Subhan (ISLAMISCHE BILDUNG: Jurnal Pendidikan Agama Islam, 2024)
This article aims to determine the Islamic religious education approach in dealing with child and adolescent delinquency. This type of research classifies qualitative research using the literature review method. Data collection was carried out through documentation methods with data analysis techniques using content analysis to analyze the content of messages and reveal symbolic meanings in primary sources. The research results show that the Islamic religious education approach in dealing with child and adolescent delinquency is carried out through selecting appropriate strategies, methods and self-management training to increase self-control in educational settings. Prevention strategies in learning are carried out by creating Islamic routines, collaboration between Islamic educators and counseling teachers, collaboration between schools, creating pleasant classroom conditions and curative strategies in learning through personal approaches and collaboration between educators and students. Cooperative learning methods provide opportunities for students to learn together. The function of educators is as a guide, facilitator and controls and directs students' learning to create an atmosphere of independent learning. Self-management is carried out in the stages of self-monitoring, self-evaluation and self-reward